(untitled) (Communication & Society, 2018)
Drawing from the research project, “eDCINEMA: Hacia el espacio digital europeo. El papel de las cinematografías pequeñas en versión original”, which was financed by the Plan Nacional de I+D+i of the Ministerio de Economía y Competitividad (Ref. CSO2012-35784) and developed by the Grupo de Estudos Audiovisuais of the Universidade de Santiago de Compostela, we set out to identify the principle barriers facing European identitarian cinema in the uncertain European digital arena, and make recommendations that will assist its promotion and circulation. Thus, in line with the quandary expressed in the title of this study, we will look at small cinemas’ role in both the recognition and the obliteration of the array of cultural singularities that make up the European identity. Concerning the Methodological Plan and its instrumental implementation, we decided on a four-party, multiphase format, that includes an extensive review of the academic, technical and institutional literature, a definition of the population under analysis, the design and execution of indepth interviews, the application of a Delphi questionnaire on a Panel of Experts, and the analysis and interpretation of data. As a conclusion to the research, we have drawn up a list of recommendations to be submitted to the pertinent institutions across Europe, which we hope will improve the circulation of European identitarian cinema and thereby consolidate it as a “smallcinema_OV” action proposal within the framework of Creative Europe 2014-2020.